A QUALITATIVE EVIDENCE SYNTHESIS OF ARTICLE ABSTRACT WRITING IN ELT AND LITERATURE JOURNALS - Sri Budiyono; Fahrus Zaman Fadhly (University of Kuningan, 2023)
Abstracts are essential components of academic research articles, providing a concise summary of the study's purpose, methods, results, and conclusions. This qualitative evidence synthesis examines the quality, structure, and content of abstracts in the fields of English Language Teaching (ELT) and Literature. A systematic search of relevant databases identified 15 peer-reviewed articles published in English with a focus on abstract writing. Thematic analysis was used to analyze the studies for their research findings, methodologies, and recommendations related to abstract writing. The findings reveal that abstracts tend to be descriptive, with a focus on presenting the research problem, methodology, and main findings. However, there is a lack of consistency in structure and content across journals, and the quality of abstracts varies widely. Based on the analysis, several key recommendations for improving abstract writing in ELT and Literature journals are proposed, including greater consistency and standardization across journals, and improved training for authors and reviewers. This qualitative evidence synthesis offers a thorough overview of the body of knowledge on the subject of writing effective abstracts for ELT and literature journals and makes suggestions for further study and practice in this field. The study highlights the need for greater attention to abstract writing quality, structure, and content, and provides practical recommendations for improving the quality of abstracts in ELT and Literature research articles using thematic analysis as a data analysis technique.